Effect of loratadine, an H1 antihistamine, on induced cough in non-asthmatic patients with chronic cough. - Tanaka, S. (1996)
BACKGROUND: H1 antihistamines have been shown to have an antitussive effect in patients with asthma, postnasal drip, and allergic rhinitis. No study has been performed to determine whether orally administered H1 antihistamines can reduce the number of coughs induced by stimulation of cough receptors in non-asthmatic patients with chronic dry cough. METHODS: The effect of loratadine (10 mg) on the number of coughs induced by ultrasonically nebulised distilled water (UNDW) was examined in 10 patients with nasal disease and in seven patients with unexplained chronic cough using a randomised, double blind crossover method. Eleven normal volunteers were also studied. Each subject inhaled UNDW for one minute, and the numbers of coughs during the one minute inhalation and the 30 seconds following it were counted. RESULTS: There was no difference in the results of pulmonary function tests performed before and one minute after UNDW inhalation for either patients or normal subjects. There was also no significant difference between the results of pulmonary function tests before or after oral administration of loratadine. Loratadine significantly reduced the number of coughs in patients with nasal disease and in those with unexplained chronic cough, but not in normal subjects. CONCLUSIONS: The H1 antihistamine loratadine reduces cough induced by UNDW. The release of histamine may contribute to the chronic cough in patients with unexplained chronic cough or nasal disease.